Sistemas de liberação de fármaco intrabolsa periodontal - Bruschi, Marcos Luciano; Panzeri, Heitor; De Freitas, Osvaldo; Guimarães Lara, Elza Helena; Gremião, Maria Palmira Daflon [UNESP] (My University, 2006)
Periodontal disease is very common in the world population. It is caused by the accumulation of microbial components of the dental biofilm inside the subgingival areas, producing an inflammatory process that affects the supporting structures of tooth, periodontal pockets and loss of the teeth, if not treated. The conventional treatment consists of tooth surface mechanical cleaning and root planning, associated or not to the systemic use of high concentrations of antibiotics, but with reduced effectiveness, and adverse effects. The patient compliance to the therapeutic is committed too. In the last decades, the treatment has been optimized for the use of drug delivery systems to the periodontal pocket, with the advantage of delivering the drug in the specific site, sustaining and/or controlling the drug concentration. Recently, the use of new drug delivery systems has been receiving great interest. This review approaches the main delivery systems for the administration of drugs to the periodontal pocket, their usefulness, as well as the available protocols for the evaluation of these systems effectiveness in the periodontal therapy.
Periodontal pocket drug delivery systems
Keywords: Delivery systems; Periodontal diseases; Periodontal pocket; Periodontal pocket delivery